Effective Universal Coverage of Diabetes Mellitus Type 2 in Chile - Sara Guerrero-Núñez; Sandra Valenzuela-Suazo; Patricia Cid-Henríquez
ABSTRACT Objective: determine the prevalence of Effective Universal Coverage of Diabetes Mellitus Type 2 in Chile and its relation with the variables: Health Care Coverage of Diabetes Mellitus Type 2; Average of diabetics with metabolic control in 2011-2013; Mortality Rate for Diabetes Mellitus; and Percentage of nurses participating in the Cardiovascular Health Program. Method: cross-sectional descriptive study with ecological components that uses documentary sources of the Ministry of Health. It was established that there is correlation between the Universal Effective Coverage of Diabetes Mellitus Type 2 and the independent variables; it was applied the Pearson Coefficient, being significant at the 0.05 level. Results: in Chile Universal Health Care Coverage of Diabetes Mellitus Type 2 (HbA1c<7% estimated population) is less than 20%; this is related with Mortality Rate for Diabetes Mellitus and Percentage of nurses participating in the Cardiovascular Health Program, being significant at the 0.01 level. Conclusion: effective prevalence of Universal Health Coverage of Diabetes Mellitus Type 2 is low, even though some regions stand out in this research and in the metabolic control of patients who participate in health control program; its relation with percentage of nurses participating in the Cardiovascular Health Program represents a challenge and an opportunity for the health system.